PENYESUAIAN DIRI, DUKUNGAN SOSIAL TEMAN SEBAYA DAN STUDENT WELL-BEING PADA MAHASISWA VOKASI PELAYARAN - Merinta Wira Ababiel; Dewi Mahastuti; Fauziah Julike Patrika (Fakultas Psikologi Universitas Hang Tuah, 2023)
This study aims to determine the relationship between self-adjustment, peer social support and student well-being in Students of the Vocational Shipping Faculty, Hang Tuah University. The research method used is quantitative. The analysis used multiple correlation. The number of respondents in this study were 180 students, selected by saturated sampling technique. This study used three scales, namely the student well-being scale (α=0.967), self-adjustment scale (α=0.835) and peer social support scale (α=0.936). The results of the study show that there is a relationship between self-adjustment and peer social support with student well-being in students of the Vocational Shipping Faculty, Hang Tuah University. The adjustment variable made an effective contribution of 43.4%, while peer social support provided an effective contribution of 42.3%.